2020
DOI: 10.3390/ijerph17197026
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Purchase Intention and Willingness to Pay for Carbon-Labeled Food Products: A Purchase Decision-Making Experiment

Abstract: Carbon labeling describes carbon dioxide emissions across food lifecycles, contributing to enhancing consumers’ low-carbon awareness and promoting low-carbon consumption behaviors. In a departure from the existing literature on carbon labeling that heavily relies on interviews or questionnaire surveys, this study forms a hybrid of an auction experiment and a consumption experiment to observe university students’ purchase intention and willingness to pay for a carbon-labeled food product. In this study, student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Mostafa [71] found that consumers in Egypt are willing to pay a price premium of approximately 75 Egyptian pounds for carbon-labeled products. For the case of Chinese consumers, see Zhao et al [72].…”
Section: Discussionmentioning
confidence: 99%
“…Mostafa [71] found that consumers in Egypt are willing to pay a price premium of approximately 75 Egyptian pounds for carbon-labeled products. For the case of Chinese consumers, see Zhao et al [72].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies typically focus on a particular product (e.g., coffee, tomatoes, light bulbs, washing machines) or product category (e.g., meat, dairy products, home appliances, building materials), which permits assessing within-product (category) effects but not substitution and spillover effects. Another important limitation is that most studies have evaluated labeling effects as self-reported willingness to pay, purchase intention, noticeability or visual attention, and preference for label designs 10,64,72,73,83 . Limited evidence is available for assessing the effects of carbon and energy labeling on actual purchasing and consumption behavior for products with high technical potential to reduce emissions (e.g., air travel), perhaps due to the difficulty of accessing actual sales data.…”
Section: Evidence Of Effectivenessmentioning
confidence: 99%
“…For example, Shuai et al [11] conducted a scenario experiment to analyze consumers' preferences and WTP for agricultural products, such as bananas and eggs, and instant noodles with low, medium, and high carbon labels. Zhao and Zhong [12] combined auction experiments with consumer experiments to observe college students' willingness to purchase and pay for food products with carbon labels. Compared with the revealed preference methods, the stated preference methods are more effective in describing market responses when the products have not yet appeared on the market, which is the case for carbonlabeled products in the Chinese market as they have not yet been widely circulated.…”
Section: Introductionmentioning
confidence: 99%